Laccase-based biocathodes: Comparison of chitosan and Nafion - Ichi-Ribault, S; Zebda, A; Laaroussi, A; Reverdy-Bruas, N; Chaussy, D; Belgacem, MN; Suherman, AL; Cinquin, P; Martin, DK (Elsevier, 2016)
Chitosan and Nafion® are both reported as interesting polymers to be integrated into the structure of 3D electrodes for biofuel cells. Their advantage is mainly related to their chemical properties, which have a positive impact on the stability of electrodes such as the laccase-based biocathode. For optimal function in implantable applications the biocathode requires coating with a biocompatible semi-permeable membrane that is designed to prevent the loss of enzyme activity and to protect the structure of the biocathode. Since such membranes are integrated into the electrodes ultimately implanted, they must be fully characterized to demonstrate that there is no interference with the performance of the electrode. In the present study, we demonstrate that chitosan provides superior stability compared with Nafion® and should be considered as an optimum solution to enhance the biocompatibility and the stability of 3D bioelectrodes.